Construction method of riparian zone wetland for reducing non-point source pollution - ZHANG CHUHUA; WANG PING; LIAO HAIBIN; LUO LIUJUN; LENG JIANXIONG; WU MIN; LI JINTAO; ZHANG LIN; HUANG JING (2017)
The invention provides a construction method of a riparian zone wetland for reducing non-point source pollution. The method comprises the steps of investigating the natural geography situation of a contaminated river, selecting the appropriate riparian zone natural wetland, and artificially reconstructing the riparian zone natural wetland so as to construct the riparian zone wetland used for reducing the non-point source pollution, wherein the artificially reconstructing method comprises the steps of arranging environment-friendly ecological slope protection components at both sides of a river bank and planting plants used for enriching pollutants in a riparian zone. A combined wetland ecosystem with functions of heavy metal pollutant interception and purification is formed in the riparian zone wetland constructed by the method, so that the ecological interception and purification for pollutants entering into the river are realized, the aim of reducing river pollutants is achieved, the self-purification abili